「平板電腦補救教學計畫」執行情形之探討 A Study on the Implementation of the "Tablet PCs as Teaching Tool in Remedial Instruction Project" - 陳琦媛 Chi-Yuan Chen (National Changhua University of Education, 2016)
本研究旨在探討國內某所私立大學師資培育中心於102 至103 學年度所推動之平板電腦補救教學計畫的執行情形。此計畫與大學鄰近四所國中合作，以大學修習教育學程之師資生擔任補救教學教師，由大學端訓練師資生使用平板電腦教學平台技術，由國中端推薦各科教師指導師資生課程設計與教學規劃，以各校參與補救教學之學生為對象，嘗試將平板電腦融入於補救教學課程中。為瞭解計畫執行情形，於計畫結束後本研究以訪談和問卷調查法收集計畫參與人員意見。於訪談方面，共有7 位國中行政主管及8 位國中教師接受訪談。於問卷調查方面，共收集20 位大學師資生、9 位國中行政主管、7 位國中教師及47 位國中學生之問卷調查結果。研究結果發現平板電腦教學確實可增加學生學習樂趣，但亦可能導致學生分心，老師需花費較多心力處理班級狀況或網路問題。若要提升整體計畫成效，需幫助師生熟悉平板電腦操作流程，並搭配良好課程設計及教學平台介面始能產生良好教學效果。整體而言，平板電腦補救教學的推動需針對課程內容與學生需求規劃具系統性之平板電腦教學計畫，並有良好網路支援環境和教學平台介面，師資生亦需加強班級經營能力。未來若國內師資培育機構欲推動相關計畫，建議可由師資培育大學教師、中學教師與師資生共同針對平板電腦及補救教學設計符合學生程度之客製化課程，將可收較良好之成效。本研究之結果可作為國內師資培育機構推動數位補救教學計畫之參考，對於未來國內推動大學師資培育機構與中學進行合作計畫之執行方 式具有實質之參考價值。 The purpose of this study was to explore the effectiveness and problems of carrying out a project using tablet PCs as teaching tools in remedial instruction. In this study, the Center of Teacher Education of the case university cooperated with four junior high schools to run a digital remedial instruction project. Pre-service education program students from the university were invited to be remedial instruction teachers, and they were trained in techniques to run the digital teaching media on tablet PCs. The collaborative schools recommended some of their teachers to act as counselors for the teaching methods and curriculum design for these college students, and a sample of students from these schools were suggested to participate in the remedial instruction class. At the end of the project, the researcher interviewed 7 administrators and 8 teachers from the collaborative schools, and invited 20 pre-service education program students together with 9 administrators, 7 teachers, and 47 students from the collaborative schools to complete a questionnaire survey. Results from this study indicated that tablet PCs can enhance students' learning interest, however, tablet PCs can be a distraction to students' attention, and teachers may have to spend more time on classroom management as well as solving internet connection problems. Overall, requirements for a successful implementation of using tablet PCs as teaching tools in remedial instruction include: the design of systematic tablet PC teaching plans based on curriculum contents and students' needs, adequate internet supporting environment and instructional platforms, and improved classroom management ability of the education program students. If teacher training institutions try to carry out similar projects in the future, it would be more effective if professors, secondary school teachers, and education program students work together to design customized curriculum materials matching students' learning needs and developmental status. The above findings could be useful reference for other teacher training institutions when they try to carry out digital remedial instruction projects. Also, the findings should be worth referring to when teacher training institutions try to work collaboratively with secondary schools.